2022
DOI: 10.1155/2022/3342910
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Breast Surgical Oncology Fellowship in the United States

Abstract: The surgical treatment of breast cancer has rapidly evolved over the past 50 years, progressing from Halsted’s radical mastectomy to a public campaign of surgical options, aesthetic reconstruction, and patient empowerment. Sparked by the research of Dr. Bernard Fisher and the first National Surgical Adjuvant Breast and Bowel Project trial in 1971, the field of breast surgery underwent significant growth over the next several decades, enabling general surgeons to limit their practices to the breast. High surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 10 He observed that most Parkland surgical residents did not have adequate exposure to managing BC; such as not performing a single radical mastectomy (standard operation for BC at that time) because patients presented to the hospital at an inoperable stage. 11 Dr. Cheek’s dream of an adequate training experience was later fulfilled by a BC patient’s generous endowment which helped establish the “Seeger Endowed Fellowship in Surgical Oncology of the Breast”. This was the first breast surgical oncology fellowship of the United States developed at the Baylor University Medical Centre in 1980.…”
Section: Introductionmentioning
confidence: 99%
“… 10 He observed that most Parkland surgical residents did not have adequate exposure to managing BC; such as not performing a single radical mastectomy (standard operation for BC at that time) because patients presented to the hospital at an inoperable stage. 11 Dr. Cheek’s dream of an adequate training experience was later fulfilled by a BC patient’s generous endowment which helped establish the “Seeger Endowed Fellowship in Surgical Oncology of the Breast”. This was the first breast surgical oncology fellowship of the United States developed at the Baylor University Medical Centre in 1980.…”
Section: Introductionmentioning
confidence: 99%